Assessment of the Absorptive Capacity for Government and Donor Funding: The Case of the DOH - Alexander Michael G. Palma (Philippine Institute for Development Studies (PIDS), 2001)
Agencies tasked to carry out a social agenda have distinct experience in the utilization of available resources. The issues that confront the DOH in the delivery of healthcare services support the need to look at the utilization of both government and donor funding in the implementation of its programs, projects and regular functions. The study attempted to provide measures for absorptive capacity of a line agency, or its capacity to utilize its legislated budget. The measures for absorptive capacity were determined for each of the public health programs, and correlated to the extent of accomplishments. Case analysis of two continuing DOH programs were made, each having different modes not only in program implementation, but in fund utilization as well. Another case study of a typical foreign-assisted project was offered, validating the observed general downtrend in foreign and domestic funding utilization. To serve as basis for future measures, institutional requirements and some insights on policies that may directly or indirectly influence utilization were identified.
Keywords: 330; health sector; Gesundheitskosten; Finanzkontrolle; Philippinen